Business Model Design and the Performance of Entrepreneurial Firms - Zott, Christoph; Amit, Raphael (Organization Science, 2007)
We focus on the design of an organization’s set of boundary-spanning transactions—business model design—and ask how business model design affects the performance of entrepreneurial firms. By extending and integrating theoretical perspectives that inform the study of boundary-spanning organization design, we propose hypotheses about the impact of efficiency-centered and novelty-centered business model design on the performance of entrepreneurial firms. To test these hypotheses, we developed and analyzed a unique data set of 190 entrepreneurial firms that were publicly listed on U.S. and European stock exchanges. The empirical results show that novelty-centered business model design matters to the performance of entrepreneurial firms. Our analysis also shows that this positive relationship is remarkably stable across time, even under varying environmental regimes. Additionally, we find indications of potential diseconomies of scope in design; that is, entrepreneurs’ attempts to incorporate both efficiency- and novelty-centered design elements into their business models may be counterproductive.